A Prediction Of Welding Process Control Variables By Prediction Of Weld Bead Geometry Using Factorial Design Approach - S, Thiruchitrambalam; SUNDARAM, HEMAVATHI; PANDEY, SUNIL (2012)
Plasma Enhanced Shielded Metal Arc Welding (PESMAW) is a modified version of the age old manual metal are welding (MMA) where the cellulose based flux coated solid wires are replaced by tubular low hydrogen flux coated electrodes. PESMAW process is aimed to eliminate the usage of cellulose in the electrode coating so as to save some trees and hence make the welding process partially green. The high heat content of the cellulose supported arc is achieved by controlled supply of auxiliary plasma gas through the tubular wire directed into the arc. This paper discusses the influence of the welding process parameters to the weld bead characteristics of weldments made by PESMAW process using mild steel as base metal. Two level fractional factorial design was adopted to investigate and quantify the direct and interactive effects of four major control parameters. “Bend on plate” technique was used to lay weldments and bead geometry was measured using standard metallurgical procedures. Statistical models were made from the obtained results and were analyzed and tested by using analysis of variance technique and students’t’ test. The main and interactive effects of control parameters were studied and presented in graphical form.